ACTUAL PEDAGOGICAL ISSUES RELATED TO YOUTH INFORMATION CULTURE - Alisher Abdulatifovich Anvarov (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2024)
This article explains how information culture and its specific features in the modern era of information culture. The social factors that determine the lack of a critical approach to the selection of necessary information among students of a special Islamic educational college have been studied. Also, based on the fact that the acquisition of information culture is a vital necessity for future imams, the author made a number of proposals and recommendations in this regard. In the article in the information society, ensuring fast and high-quality circulation of information in the education system becomes the main criterion for the progress and development of the country, and also analyzes in detail the need for the effective use of information in the field of education. The scientific article presents an analysis of studies conducted on the culture of using the Internet and social networks among students studying in secondary specialized educational institutions. This is a scientific study not only in Uzbekistan, but also in all countries of Central Asia; the formation of the information culture of students in secondary specialized Islamic educational colleges has not been studied at all. Formation criteria have been developed and explained in detail information culture of students studying in secondary specialized Islamic educational colleges